Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Pada RS.Pku Muhammadiyah Boyolali - Nugroho, Eko Yanuar; , Ahmad Mardalis, SE.,MBA (2016)
This study aimed to analyze the effect of tangible, responsiveness, assurance, empathy, and reliability influence on patient satisfaction in the use of hospital services PKU Muhammadiyah Boyolali . The sampling method is based on convenience sampling technique ,ie selecting samples that are not limited and researchers have certain criteria in sampling , in which the author directly gave questionnaires to respondents that appropriate criteria. The results of this study indicate that in partial tangible, responsiveness, assurance, empathy and reliability positive and significant impact on patients' satisfaction in using hospital services PKU Muhammadiyah Boyolali , while in simultaneous all independent variables significantly influence patient satisfaction at PKU Muhammadiyah Boyolali